2002
DOI: 10.1002/mop.10147
|View full text |Cite
|
Sign up to set email alerts
|

Broadband hybrid microstrip couplers—Amplitude and phase

Abstract: Higher order interpolatory vector bases for computational electromagnetics, Ž . ABSTRACT: Se¨eral designs for a 180Њ hybrid coupler are discussed. Using the stepped-impedance method, the bandwidth of an 11 GHz hybrid coupler is increased to approximately 1.6 times the bandwidth of a con¨entional hybrid coupler. Comparisons are made between con¨entional and broadband hybrid couplers, as well as between circular and rectangular designs, and the phase beha¨ior of each is compared for the first time. ᮊ ABSTRACT: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…It was found that the bandwidth is less than that of the three-port FCL circulator, which was between 9 and 12 GHz. This is due to the limiting bandwidth of the hybrid coupler, which has a bandwidth of 3 GHz at 27% of the design frequency as reported in [10]. The measurements confirm the nonreciprocal behavior of the four-port FCL circulator, and an example is shown in Figure 9.…”
Section: B Four-port Fcl Circulatorsupporting
confidence: 76%
See 1 more Smart Citation
“…It was found that the bandwidth is less than that of the three-port FCL circulator, which was between 9 and 12 GHz. This is due to the limiting bandwidth of the hybrid coupler, which has a bandwidth of 3 GHz at 27% of the design frequency as reported in [10]. The measurements confirm the nonreciprocal behavior of the four-port FCL circulator, and an example is shown in Figure 9.…”
Section: B Four-port Fcl Circulatorsupporting
confidence: 76%
“…Also, the effect on the conductor loss that would result from reducing the strip separation and decreasing their length requires further consideration, in addition to the effect on the bandwidth. The bandwidth of the four-port FCL circulator can be improved by replacing the conventional hybrid coupler with a broadband design [10]. The improved design of airbridges is reported in [11].…”
Section: Discussionmentioning
confidence: 99%